Does being international make companies more sustainable? Evidence based on corporate sustainability indices - Mehmet Ali Soytas; Asya Atik (Central Bank Review (CBR), 2018)
The existing literature on the relationship between corporate sustainability performance and being a domestic or international company doubt on which type of operating has more potential to be corporate sustainable. It might be expected that two types of firms can have different advantages. We take this as an empirical question and bring it to data to find an answer. We created a methodology to compare the corporate sustainability level of different companies. In this methodology, we developed different internationality indices and evaluate the effects of those on corporate sustainability. We used firm level financial variables, time and firm effects for controlling some aspects of firm heterogeneity. We estimate the indices of the internationality using the performance ratings from MSCI KLD 400 Social Index and financial information from Wharton Research Data Services' COMPUSTAT dataset. Our results present empirical evidence to support the hypothesis that being an international firm is increasing the sustainability of the company on average. Furthermore, to better understand the mechanism of this result, we examined the effect of being international separately for the factors (these are named as strengths and concerns in KLD) that increase and decrease the sustainability score of the companies respectively. We found surprisingly that being an international firm increases both strengths and concerns more compared to a domestic firm. This suggests that international companies perform higher standards on the strengths but also face hard time to reduce the concerns due to possibly multiple regulations that they face, or coordination issues in different counties etc.
Keywords: 330; Corporate sustainability; Internationality; MSCI KLD 400 social index ratings; Compustat